How can African agriculture adapt to climate change: Climate Change Impacts on Food Security in Sub-Saharan Africa: Insights from Comprehensive Climate Change Modeling - Ringler, Claudia; Zhu, Tingju; Cai, Ximing; Koo, Jawoo; Wang, Dingbao (International Food Policy Research Institute, 2011)
According to the Fourth Assessment Report of the Intergovernmental Panel on Climate Change, warming in Sub-Saharan Africa (SSA) is expected to be greater than the global average, and rainfall will decline in certain areas. Global circulation models (GCMs), which provide an understanding of climate and project climate change, tend to agree that temperatures are increasing across the region, but models vary widely regarding predicted changes in precipitation—with the exception of some agreement that precipitation decreases from June to August in southern Africa and increases from December to February in eastern Africa. Whether the Sahel will be more or less wet in the future remains uncertain. Given the limited agreement of GCMs, the University of Illinois and the International Food Policy Research Institute (IFPRI) developed a global comprehensive climate change scenario combining 17 models selected for their past performance in predicting temperature and precipitation.